Arabidopsis SME1 Regulates Plant Development and Response to Abiotic Stress by Determining Spliceosome Activity Specificity. Issue 2 (31st January 2019) - Huertas, Raul; Catalá, Rafael; Jiménez-Gómez, José M.; Mar Castellano, M.; Crevillén, Pedro; Piñeiro, Manuel; Jarillo, José A.; Salinas, Julio
Abstract : SME1 has a critical role in plant development and interaction with the environment by ensuring adequate splicing of specific precursor-messenger RNAs. Abstract: The control of precursor-messenger RNA (pre-mRNA) splicing is emerging as an important layer of regulation in plant responses to endogenous and external cues. In eukaryotes, pre-mRNA splicing is governed by the activity of a large ribonucleoprotein machinery, the spliceosome, whose protein core is composed of the Sm ring and the related Sm-like 2-8 complex. Recently, the Arabidopsis ( Arabidopsis thaliana ) Sm-like 2-8 complex has been characterized. However, the role of plant Sm proteins in pre-mRNA splicing remains largely unknown. Here, we present the functional characterization of Sm protein E1 (SME1), an Arabidopsis homolog of the SME subunit of the eukaryotic Sm ring. Our results demonstrate that SME1 regulates the spliceosome activity and that this regulation is controlled by the environmental conditions. Indeed, depending on the conditions, SME1 ensures the efficiency of constitutive and alternative splicing of selected pre-mRNAs. Moreover, missplicing of most targeted pre-mRNAs leads to the generation of nonsense-mediated decay signatures, indicating that SME1 also guarantees adequate levels of the corresponding functional transcripts. In addition, we show that the selective function of SME1 in ensuring appropriate gene expression patterns through the regulation of specific pre-mRNA splicing is essential for adequate plant development and adaptation to freezing temperatures. These findings reveal that SME1 plays a critical role in plant development and interaction with the environment by providing spliceosome activity specificity.